2006
DOI: 10.1111/j.1365-246x.2005.02839.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dahuiyeh (Zarand) earthquake of 2005 February 22 in central Iran: reactivation of an intramountain reverse fault

Abstract: S U M M A R YWe used seismic body waves, radar interferometry and field investigation to examine the source processes of the destructive earthquake of 2005 February 22 near Zarand, in south-central Iran. The earthquake ruptured an intramountain reverse fault, striking E-W and dipping north at ∼60• to a depth of about 10 km. It produced a series of coseismic scarps with up to 1 m vertical displacement over a total distance of ∼13 km, continuous for 7 km. The line of the coseismic ruptures followed a known geolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 27 publications
(27 reference statements)
2
59
0
Order By: Relevance
“…Studies of recent Iranian earthquakes have demonstrated that many have occurred on previously unrecognized active faults (e.g. Talebian et al 2004Talebian et al , 2006. In urban areas, the identification and characterization of active faults is further limited by human activity, and yet the combined use of historical aerial imagery and modern satellite-derived digital topography data can help to overcome those challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of recent Iranian earthquakes have demonstrated that many have occurred on previously unrecognized active faults (e.g. Talebian et al 2004Talebian et al , 2006. In urban areas, the identification and characterization of active faults is further limited by human activity, and yet the combined use of historical aerial imagery and modern satellite-derived digital topography data can help to overcome those challenges.…”
Section: Discussionmentioning
confidence: 99%
“…The Kuh Banan Fault is seismically active Talebian et al, 2006). Numerous earthquakes have been recorded (Fig.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…1b), including the M s 5.8 Bob-Tangol earthquake at 30.9ºN 56.6ºE on 19 th December 1977 and other large events in 1933 and 1978 on the northern section of the fault. Earthquakes have also occurred on nearby faults, including the Dahuiyeh thrust which ruptured in 2005 (Talebian et al, 2006) and the Behabad fault .…”
Section: Tectonic Settingmentioning
confidence: 99%
“…Where available, we use published earthquake depths and mechanisms from this technique (Laane and Chen, 1989;Byrne et al, 1992;Baker, 1993;Berberian et al, 2000;Maggi et al, 2000;Berberian et al, 2001;Jackson et al, 2006;Talebian et al, 2006;Engdahl et al, 2006;Nissen et al, 2010Nissen et al, , 2011Walker et al, 2013;Barnhart et al, 2014b;Jolivet et al, 2014;Penney et al, 2015). In addition, we have used teleseismic P and SH bodywaveform modelling to determine the depths and focal mechanisms of 7 earthquakes for which solutions have not previously been published.…”
Section: Earthquake Compilationmentioning
confidence: 99%